Zur Poetik des Lyrikers Konstantin M. Fofanov - Fenner, Ingrid (Slavistische Beitraege, 1998)
The present work is dedicated to the study of the artistic work of the Russian poet Konstantin Michajlovič Fofanov (1862 - 1911). He was one of the best-known, if not the most famous and beloved poets in Russia in the eighties. The oeuvre Fofanovs may also claim an interest in being examined in a monographic representation, since the poet was not only a fashionable mass author, but was also regarded as pioneer and appreciated by more important, especially symbolist poets.